Penerapan Model Realistic Mathematic Education (RME) untuk Meningkatkan Hasil Belajar pada Pembelajaran Matematika - Wasiul Muarif; Mustaqimah; Ary Prasetyawati; Suryani Suryani; Titik Maryati; Siti Rokhimah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Learning outcomes are a crucial indicator in the educational process, as they not only establish a strong academic foundation but also contribute to the development of essential life skills relevant to future demands. One instructional model considered effective in supporting these achievements is Realistic Mathematics Education (RME), which emphasizes conceptual understanding through meaningful and real-life contexts for students. This research uses a qualitative approach. The research subjects are mathematics teachers at the aforementioned schools. The informants in this study are mathematics teachers. Data were collected through interviews, observation, and documentation. The findings of the study are as follows: 1) The steps of the RME model include understanding contextual problems in learning materials, explaining the contextual problems, solving the contextual problems, comparing and discussing answers, and drawing conclusions; 2) The advantages of the RME model are enhancing students’ conceptual understanding, encouraging mathematical thinking, developing mathematical modeling skills, and fostering reflective and collaborative attitudes; 3) The disadvantages of the RME model include difficulties in finding suitable contextual problems, the incompatibility of certain mathematical topics with contextualization, the requirement for high teacher competence, longer instructional time, and more complex assessment processes. The conclusion of this study is that the Realistic Mathematics Education (RME) model can be implemented in the teaching process as an effort to improve learning outcomes at the Madrasah Tsanawiyah or lower secondary school level.